2022
DOI: 10.1186/s13223-022-00700-3
|View full text |Cite
|
Sign up to set email alerts
|

Nasal mucosal reactivity assessment via a double-blind placebo-controlled food challenge with cow’s milk allergens

Abstract: Background Allergies, including food allergies, are a considerable clinical and public-health problem. The introduced preventive measures and differential diagnostics, including oral food challenges, are the gold standard for determining further treatment planning. Case presentation We present a case of an 18-year-old girl with a cow’s milk allergy who underwent an oral food challenge (double blind oral food challenge). Such a challenge may be conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The results confirmed the usefulness of NPT in the diagnosis of food allergy to shrimp [ 21 ]. The work of Gelis et al was an inspiration for our team, and in our study in 2020 we confirmed the reactivity of the nasal mucosa during the oral provocation test with cow's milk protein allergens [ 22 ]. In our current study in the diagnosis of food allergy, in addition to the recognized diagnostic method (i.e., DBPCFC), we used a new diagnostic method (NPT) with chicken egg protein, and confirmed its effectiveness and safety.…”
Section: Discussionsupporting
confidence: 74%
“…The results confirmed the usefulness of NPT in the diagnosis of food allergy to shrimp [ 21 ]. The work of Gelis et al was an inspiration for our team, and in our study in 2020 we confirmed the reactivity of the nasal mucosa during the oral provocation test with cow's milk protein allergens [ 22 ]. In our current study in the diagnosis of food allergy, in addition to the recognized diagnostic method (i.e., DBPCFC), we used a new diagnostic method (NPT) with chicken egg protein, and confirmed its effectiveness and safety.…”
Section: Discussionsupporting
confidence: 74%